SYNERGY OF INTELLECTUAL CAPITAL AND SHARIA FINANCIAL CAPITAL IN IMPROVING FINANCIAL PERFORMANCE - Albahi, Muhammad; Yuslem, Nawir; Soemitra, Andri; Noor, Mohd (TRIKONOMIKA, 2024)
This study aims to analyze the influence of Intellectual Capital and Sharia Financial Capital on the financial performance of companies listed in the Jakarta Islamic Index (JII) and to evaluate the synergy between the two capitals in increasing competitiveness and business sustainability. The data used are from the annual reports of JII companies during the period 2020–2024. Intellectual Capital is measured using the Value-Added Intellectual Coefficient (VAIC) model, and Sharia Financial Capital, which includes the zakat ratio, profit-sharing ratio, and Sharia debt ratio. Financial performance is measured using Return on Equity (ROE), Return on Assets (ROA), and Price-to-Book Value (PBV). The results show that Intellectual Capital and Sharia Financial Capital have a positive influence on financial performance. The synergy between Intellectual Capital and Sharia Financial Capital has been proven to have a significant impact, creating a substantial competitive advantage in the context of Maqashid Sharia.